Principled Faithfulness: A Measure of Moral Reasons for Fidelity and Its Associations with the Tendency to Engage in Extramarital Relationships, Moral Emotions and Emotion Regulation - Carmen Gabriela Lișman; Andrei Corneliu Holman (Social Sciences)
The prevalence of infidelity is high, although it can have destructive impacts on marital relationships. Most past research has focused on utilitarian concerns against extramarital behavior, analyzing the motivational forces that either deter or foster infidelity as a function of the rewards and costs that unfaithful behavior would involve for the individual. The present research (total N = 1067 Romanian married participants) aimed to highlight the intrinsic moral concerns that deter infidelity in marital relationships by applying the general framework of the Moral Foundations Theory (MFT). The first study developed a measure of the moral reasons for fidelity and examined its dimensions and psychometric properties. The second study investigated its factorial validity and its relationships with the actual tendency to engage in unfaithful behaviors, the intensity of moral emotions toward infidelity, and the use of different emotion regulation strategies. Overall, the results suggest four types of moral reasons for fidelity: heeding rules, reciprocal ownership, loyalty, and decency and nonmaleficence, and the new scale emerged as having satisfactory psychometric proprieties. Higher scores were positively associated with moral disgust, anger, and contempt toward unfaithful marital partners and compassion toward their spouses, as well as cognitive reappraisal and endorsement of the five moral domains described by MFT. Also, married individuals scoring higher on this measure were also found to have a lower propensity toward infidelity. These findings pinpoint a fine-grained outline of the moral underpinnings of fidelity and indicate their potential relevance for the actual tendency to engage in extramarital relations.